2009
DOI: 10.1590/s0066-782x2009000800015
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida e indicadores clínicos na insuficiência cardíaca: análise multivariada

Abstract: SummaryBackground: In Heart Failure (HF), special attention must be given not only to objective or isolated aspects, but also to the patient's health self-perceptions. Subjective aspects can help healthcare providers understand and better treat HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…It is believed that a greater number of patients between different FCs may correlate with the questionnaire used in this study, such as the study by Santos et al (2009), who found less impact in FC I in comparison with FC III. The emotional and physical factors are dimensions that influence the patients' quality of life with HF (Dourado et al, 2006;Peters-Klim et al, 2010).…”
Section: Quality Of Lifementioning
confidence: 93%
“…It is believed that a greater number of patients between different FCs may correlate with the questionnaire used in this study, such as the study by Santos et al (2009), who found less impact in FC I in comparison with FC III. The emotional and physical factors are dimensions that influence the patients' quality of life with HF (Dourado et al, 2006;Peters-Klim et al, 2010).…”
Section: Quality Of Lifementioning
confidence: 93%
“…This limitation is closely connected to the activities of daily living of the elderly, to quality of life (QL), and to changes in the lifestyle imposed by the disease. Patients with HF have their lives affected by the disease and even optimized care seems to have impacts on their quality of life (8) .…”
Section: Introductionmentioning
confidence: 99%
“…. The measurements of quality of life (QOL) in most of the studies have been performed based on the hospital setting and discharge follow-up (McMurray et al, 2012;Naveiro-Rilo et al, 2010;Santos, Plewka, & Brofman, 2009).…”
mentioning
confidence: 99%